2017
DOI: 10.1186/s41065-017-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitogenome of Orcula dolium (Draparnaud, 1801); ultra-deep sequencing from a single long-range PCR using the Ion-Torrent PGM

Abstract: BackgroundWith the increasing capacity of present-day next-generation sequencers the field of mitogenomics is rapidly changing. Enrichment of the mitochondrial fraction, is no longer necessary for obtaining mitogenomic data. Despite the benefits, shotgun sequencing approaches also have disadvantages. They do not guarantee obtaining the complete mitogenome, generally require larger amounts of input DNA and coverage is low compared to sequencing with enrichment strategies. If the mitogenome could be amplified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…From annotated, previously published sequences (accession numbers NC_001816, NC_021747 and NC_017872), we extracted the individual genes following the annotation in the NCBI RefSeq database. However, previous studies, which used the sequence of Ce.nemoralis in mitogenomic phylogenetic analyses, repeatedly resulted in a spuriously long branch for this species (Knudsen et al 2006, González et al 2016, Minton et al 2016, Groenenberg et al 2017). A closer examination of the mitogenome sequence and translation of its protein coding regions revealed a very low quality of the sequence (see also White et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From annotated, previously published sequences (accession numbers NC_001816, NC_021747 and NC_017872), we extracted the individual genes following the annotation in the NCBI RefSeq database. However, previous studies, which used the sequence of Ce.nemoralis in mitogenomic phylogenetic analyses, repeatedly resulted in a spuriously long branch for this species (Knudsen et al 2006, González et al 2016, Minton et al 2016, Groenenberg et al 2017). A closer examination of the mitogenome sequence and translation of its protein coding regions revealed a very low quality of the sequence (see also White et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial genome sequences may then become handy for primer design, to facilitate assembly of further mitochondrial genomes from outputs of high-throughput sequencing, or directly as the data for phylogenetic analyses. In fact, one of the best resolved backbone phylogenies of Stylommatophora to date was reconstructed from mitochondrial genome sequences (Groenenberg et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses of the stylommatophoran mitogenomes (González et al 2016;Romero et al 2016) showed them in a well-supported clade among Panpulmonata (with PP and bootstrap values 1 and 99, respectively). Previous mitogenome phylogenies of stylommatophoran superfamilies (Groenenberg et al 2017;Harasewych et al 2017;Yang et al 2019;Doğan et al 2020) showed a clade of Helicoidea separate from other superfamilies, although mitogenomes of only 11 stylommatophoran superfamilies (Yang et al 2019) out of 26 listed by Bouchet et al (2017) are represented in GenBank. According to Bouchet et al (2017), Helicoidea includes 17 families but hitherto phylogenetic relationships could be analysed only for three or four of them, namely Helicidae, Camaenidae, Geomitridae, and Polygyridae (González et al 2016;Lin et al 2016;Minton et al 2016a;Harasewych et al 2017;Doğan et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial DNA genome is widely used in several research fields, including genetics, evolution, and species genetic diversity, due to its unique structural features and genetic characteristics (Brown et al, 1982;Wang et al, 2019;Zhang et al, 2021), and it has become a very important molecular genetics tool. The mitochondrial genome has been widely used in the study of genetic variation and phylogeny of gastropod populations (Grande et al, 2008;Groenenberg et al, 2012;Groenenberg et al, 2017). Mitochondrial cytochrome oxidase (COI) genes in mitochondrial DNA are very conserved and highly homologous and are often used to analyze and explore population phylogenetic relationships (Miya et al, 2001).…”
Section: Introductionmentioning
confidence: 99%